Tribal and chiefly warfare in South America - Redmond, Elsa M. (Studies in Latin American ethnohistory & archaeology, 1994)
"Preparations, organization, weapons, strategies, rituals, and mortuary treatments associated with warfare among contemporary Jivaro and Yanomamo, and among contact-period Colombian and Panamanian chiefdoms, provide criteria for differentiating tribal and chiefdom levels; these are evaluated using archaeological data from various regions and periods"--Handbook of Latin American Studies, v. 57.